Tolerance mechanisms of two species of Indocalamus under soil Pb stress and the effects of rhizosphere environmental factors on tolerance - Yedan Gao; Mingyan Jiang; Yixiong Yang; Sujia Wang; Chen Chen; Zhenghua Luo; Bingyang Lyu; Qibing Chen (Ecotoxicology and Environmental Safety, 2025)
Currently, phytoremediation technology is widely used in the management of Pb-contaminated soil, and plants with high Pb tolerance can adapt to the environment through tolerance mechanisms, which can promote the sustainable development of soil health. In this study, we revealed the Pb tolerance of two species of Indocalamus in different levels of Pb-contaminated soil (0, 500 and 1500 mg/kg) and the effects of rhizosphere environmental factors on tolerance. The BCF and TF of Ped (Indocalamus pedalis) did not change with increasing concentration, whereas the TF of Kun (Indocalamus kunmingensis) decreased to reduce the upwards transport of Pb, and the GSH content of Kun clearly increased. Pb in plant cells was distributed mainly in the cell wall of Kun, as well as in the roots, whips, and stems of Ped, whereas Pb in the leaves of Ped was distributed mainly in the vesicles. In terms of Pb forms, the proportion of highly toxic Pb was greater in Ped than in Kun, which was attributed mainly to its transport through stems. In terms of the rhizosphere environment, the rhizobacteria of Ped contributed to only higher Aci-Pb ratios, and the rhizobacteria of Kun led to an increase in the overall amount of Pb available for uptake by the plant. Overall, Kun was more tolerant to Pb in Pb-contaminated soil than Ped was. Kun tolerated Pb stress in the following four main ways: 1) limiting Pb to underground parts, 2) increasing physiological tolerance, 3) blocking Pb outside the cell wall, and 4) decreasing Pb toxicity. In addition, rhizobacteria affected Pb uptake to different degrees by promoting Pb activation in the rhizosphere soil. Therefore, Kun can be used as a potential plant for the remediation of Pb-contaminated soil, and the results of this study further provide some guidance for improving Kun remediation efficiency.